Towards a more comprehensive policy mix conceptualization for environmental technological change: A literature synthesis - Karoline S. Rogge; Kristin Reichardt (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2013)
Reaching a better understanding of the politics and policies of transitions presents a main agenda item in the emerging field of sustainability transitions. One important requirement for these transitions, such as the move towards a decarbonized energy system, is the redirection and acceleration of technological change, for which policies play a key role. Several studies of policies supporting environmental technological change have argued for the need to combine different policy instruments in so-called policy mixes. However, existing policy mix studies often fall short of reflecting the complexity and dynamics of actual policy mixes, and they lack a common terminology. In this paper we take a first step towards a more comprehensive policy mix concept for environmental technological change based on a review of the bodies of literature on innovation studies, environmental economics and policy analysis. The concept we develop consists of the three building blocks elements, processes and dimensions and introduces a clear terminology, which is particularly important for the characteristics of such a policy mix, including the consistency of its elements and the coherence of its processes. Throughout the paper, we illustrate the concept using the example of the policy mix for fostering the transition of the German energy system to renewable power generation technologies. We argue that the proposed concept provides an interdisciplinary analytical framework for empirical studies analyzing the impact of the policy mix on environmental technological change and may thereby contribute to reaching a better understanding of the politics and policies of sustainability transitions. Finally, we derive policy implications and suggest avenues for future research.
Keywords: 330; policy mix; policy strategy; instrument mix; policy making and implementation; consistency; coherence